Peran Mahasiswa Kampus Mengajar dalam Adaptasi Teknologi Canva terhadap Guru di SD Negeri 3 Tunahan - Dian Nur Fajriyah; Erna Zumrotun; Syailin Nichla Choirin Attalina (Qalam : Jurnal Ilmu Kependidikan, 2023)
The Teaching Campus Program is an implementation of Merdeka Belajar Kampus Merdeka (MBKM) and aims to assign students to support teaching and learning activities at elementary schools, one of which is SD Negeri 3 Tunahan. In its implementation, students are involved and responsible for helping schools in the fields of literacy, numeracy, and technological adaptation. The focus of this research is on the role of Teaching Campus Students on technology adaptation, especially the Canva application for teachers at SD Negeri 3 Tunahan. The purpose of this research is to find out about the role of Teaching Campus Students on the adaptation of Canva technology to teachers at SD Negeri 3 Tunahan and the impact on teachers after assistance from teaching campus students. Data collection techniques in this study include observation, interviews, questionnaires, and documentation. As for data analysis techniques, the steps include data collection, reducing data, presenting data, drawing conclusions. The results of the study show that the assistance of the Canva application to teachers has a significant impact such as teachers becoming more confident and interested in developing skills in utilizing technology, for example the Canva application when carrying out performance. Keywords : Technology Adaptation, Canva Application, Teachers